Treatment of Bartter syndrome. Unsolved issue - Carla Lessa Pena Nascimento; Cecilia Lopes Garcia; Benita Galassi Soares Schvartsman; Maria Helena Vaisbich (Elsevier, 2014)
Objective: To describe the results of a long-term follow-up of Bartter syndrome patients treated with different drugs. Method: Patients were diagnosed according to clinical and laboratory data. Treatment protocol was potassium supplementation, sodium, spironolactone, and non-steroidal anti-inflammatory drug. Patients who developed proteinuria were converted to angiotensin conversion enzyme inhibitor. The variables evaluated for each drug were Z-score for weight and stature, proteinuria, creatinine clearance, gastrointestinal complaints, amount of potassium supplementation, serum potassium and bicarbonate levels, and findings of upper digestive endoscopy. Results: 20 patients were included. Follow-up was 10.1 ± 5.2 years. 17 patients received indomethacin for 5.9 ± 5.3 years; 19 received celecoxib, median of 35 months; and five received enalapril, median of 23 months. During indomethacin, a statistically significant increase was observed in the Z-score for stature and weight, without a change in the creatinine clearance. Seven of 17 patients had gastrointestinal symptoms, and upper digestive endoscopy evidenced gastritis in three patients and gastric ulcer in four patients. During celecoxib use, a significant increase was detected in the Z-score for stature and weight and a reduction of hyperfiltration; seven patients presented gastrointestinal symptoms, and upper digestive endoscopy evidenced mild gastritis in three. During enalapril use, no significant changes were observed in the Z-score for stature, weight and creatinine clearance. The conversion to enalapril resulted in a significant reduction in proteinuria. Conclusion: The authors suggest starting the treatment with celecoxib, and replacing by ACEi if necessary, monitoring the renal function. The safety and efficacy of celecoxib need to be assessed in larger controlled studies. Resumo: Objetivo: Descrever os resultados de um acompanhamento de longo prazo de pacientes com síndrome de Bartter tratados com diferentes medicamentos. Método: Pacientes diagnosticados segundo os dados clínicos e laboratoriais. Protocolo de tratamento: suplementação de potássio, sódio, espironolactona e medicamento anti-inflamatório não esteroidal. Os pacientes que desenvolveram proteinúria foram submetidos a inibidor da enzima de conversão da angiotensina. As variáveis avaliadas durante o uso de cada medicamento foram: escore Z para peso e estatura, proteinúria, depuração da creatinina, queixas gastrointestinais, quantidade da suplementação de potássio, níveis séricos de potássio e bicarbonato e achados da endoscopia digestiva alta. Resultados: Foram incluídos 20 pacientes. O acompanhamento foi de 10,1±5,2 anos. No total, 17 pacientes receberam indometacina por 5,9±5,3 anos, 19 receberam celecoxib por aproximadamente 35 meses e cinco receberam enalapril por aproximadamente 23 meses. Durante o uso de indometacina, observamos um aumento estatístico significativo no escore Z para estatura e peso, sem alteração na depuração da creatinina. 7/17 pacientes apresentaram sintomas gastrointestinais, e a endoscopia digestiva alta mostrou gastrite em três pacientes e úlcera gástrica em quatro. Durante o uso de celecoxib, detectamos um aumento significativo no escore Z para estatura e peso e uma redução da hiperfiltração; sete pacientes apresentaram sintomas gastrointestinais e a endoscopia digestiva alta mostrou gastrite leve em três pacientes. Durante o uso de enalapril, não observamos alterações significativas no escore Z para estatura, peso e depuração da creatinina. A mudança da medicação para enalapril resultou em uma redução significativa na proteinúria. Conclusão: Sugerimos iniciar o tratamento com celecoxib e, caso necessário, substituí-lo por ACEi, monitorando a função renal. A segurança e a eficácia do celecoxib precisam ser comprovadas com grandes estudos controlados. Keywords: Bartter syndrome, Non-steroidal anti-inflammatory drug, Enalapril, Proteinuria, Palavras-chave: Síndrome de Bartter, Medicamento anti-inflamatório não esteroide, Enalapril, Proteinúria